Obtenção do sistema nanoestruturado livre de chumbo (Na0,5Bi0,5)0,94Ba0,06TiO3 (NBT-BT6) via rotas químicas - Silva, Gislayne Rayane Alves da (Universidade Federal de São Carlos, 2020)
Perovskites based on sodium bismuth titanate (Na0.5Bi0.5TiO3) are promising candidates for replacing some ceramic materials based on lead due to piezoelectric properties. The solid solution 0.94(Na0.5Bi0.5)TiO3-0.06BaTiO3 (NBT-BT6) can be highlighted as it shows the morphotropic phase boundary in this composition, where its dielectric and ferroelectric properties are maximized, as well as the piezoelectric coefficient. Most studies report the solid-state reaction as a method of obtaining this nanostructured system, which compromises its stoichiometry. Thus, this dissertation aims at the study the achievement of the NBT-BT6 through conventional hydrothermal synthesis and microwave-assisted routes and polymeric precursor - Pechini. In the hydrothermal synthesis, the study of the variation of the mineralizing concentration , time and temperature was carried out, whereas in the polymeric precursor - Pechini method, the temperature of the heat treatment of the dehydrated resin was the analyzed variable. In powders obtained under hydrothermal conditions, both conventionally and assisted by microwaves, the presence of the NBT and BT phases, and the anatase and brookite phases, after synthesis, were identified. Particles in cubic shapes and fibers were formed in both synthesis methods. The powders obtained via microwave-assisted hydrothermal route showed particles with a smaller average size and morphology with a greater presence of fibers, obtained in only 4% of the synthesis time, and after sintering at 900 °C for 2 hours they presented the NBT- BT6 phase and relative density of 87%. In samples synthesized by the polymeric precursor -Pechini method, the NBT-BT6 phase without secondary phases was obtained at 650 °C. In addition, the transformation of the phase at 260 °C, from rhombohedral to tetragonal, was observed for the formation of the solid solution NBT-BT6 indicating the presence of the morphotropic phase boundary and the beginning of crystallization at 450 °C, the lowest temperature reported in the literature.
Achievement of the nanostructured lead-free system (Na0.5Bi0.5)0.94Ba0.06TiO3 (NBT-BT6) by chemical routes
Keywords: Síntese; Hidrotermal micro-ondas; Precursor polimérico - Pechini; Hidrotermal convencional; NBT-BT6; Synthesis; Microwave hydrothermal; Polymeric precursor; Conventional hydrothermal; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS